Trunk, Mass Grasp, Knee, and Hip Muscle Performance in CrossFit Participants: Reference Values According to Participants' Sex and Limb Dominance - Ana Luiza R Rodrigues; Renan A. Resende; Livia S. Pogetti; Thiago R. T. Santos; Henrique M. P. Faria; Mauro H. Chagas; Juliana M Ocarino (North American Sports Medicine Institute, 2023)
# Background CrossFit is characterized by a diverse range of exercises recruiting different muscles and requiring different muscle functions. A characterization of muscular performance parameters in this population is needed. # Purpose To determine reference values for various aspects of muscular performance of muscles of the trunk, thigh, hip, and mass grasp in CrossFit participants. Also, this investigation aimed to compare the strength measures between male and female CrossFit participants, as well as between dominant and non-dominant limbs. # Design Descriptive, Cross-sectional. # Setting Laboratory. # Methods Isometric strength of trunk extensors (TE) and mass grasp was measured with handheld and Jamar dynamometer respectively. An isokinetic dynamometer was used to assess the muscle performance of the knee flexors (KF) and extensors (KE) (at 60º/s and 300º/s), and hip flexors (HF), extensors (HE), and abductors (HA) (60º/s and 240º/s ). Reference values for torque, work, power, fatigue, flexor:extensor ratio for the knee (hamstring:quadriceps - H:Q) and hip (HF:HE) joints were calculated. The torque and work values were normalized by the body mass. Mixed multivariate and univariate analyses of variance and independent t-tests were used for statistical analyses to compare between sexes and limbs. # Results Participants included 111 individuals (58 males and 53 females) with at least one year of experience in CrossFit. Normative data are provided for the outcome variables. Males had greater values of muscular performance parameters than females in most variables (p\<0.05). Also, the dominant limb had greater mass grasp strength (p\<0.002), greater KE power at 60º/s (p=0.015), lower H:Q ratio at 60º/s (p=0.021) and 300º/s (p=0.008), and lower KE fatigue (p=0.002). # Conclusion This study provides reference values for the trunk extensors, mass grasp, knee, and hip muscle performance in male and female CrossFit practitioners. Their muscle performance profile was characterized by few inter-limb asymmetries, and males demonstrated greater muscular performance outcomes than females, even after normalization by body mass. These reference values can be used for comparisons in research and clinical settings. # Level of Evidence 3b